2017
DOI: 10.1158/0008-5472.can-16-2434
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Hierarchy as a Determinant of Tumor Sensitivity to Chemotherapy

Abstract: Chemotherapy has been shown to enrich cancer stem cells in tumors. Recently, we demonstrated that administration of chemotherapy to human bladder cancer xenografts could trigger a wound-healing response that mobilizes quiescent tumor stem cells into active proliferation. This phenomenon leads to a loss of sensitivity to chemotherapy partly due to an increase in the number of tumor stem cells, which typically respond to chemotherapy-induced cell death less than more differentiated cells. Different bladder cance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 33 publications
(64 reference statements)
1
21
0
Order By: Relevance
“…Chemotherapy-induced death of more differentiated cells resulted in a wound healing type response that is mediated by PGE2 and that resulted in the activation and proliferation of CSCs during treatment. A mathematical model of these treatment dynamics confirmed that this wound-healing response could contribute to the amplification of the CSC population during chemotherapy [11]. At the same time, however, the model showed that this CSC enrichment was not maintained following cessation of therapy.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Chemotherapy-induced death of more differentiated cells resulted in a wound healing type response that is mediated by PGE2 and that resulted in the activation and proliferation of CSCs during treatment. A mathematical model of these treatment dynamics confirmed that this wound-healing response could contribute to the amplification of the CSC population during chemotherapy [11]. At the same time, however, the model showed that this CSC enrichment was not maintained following cessation of therapy.…”
Section: Introductionmentioning
confidence: 82%
“…At the same time, however, this interesting observation has brought up a number of questions that can best be answered by using mathematical models to interpret the data. Mathematical modeling [11] suggested that the wound-healing response alone cannot result in CSC enrichment that is sustained beyond the treatment phase, and hence cannot ex- When considering a specific model, as has been done in much of the literature so far, results can depend on the particular mathematical formulation of feedback interactions. These particular formulations are typically arbitrary, and the same biological processes can often be described by somewhat different mathematical terms, which can impact model predictions and thus lead to robustness issues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations